2018
DOI: 10.1021/acscatal.8b00584
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Catalytic CO2 Dry Reforming of Methane on Ni-Si/ZrO2 Catalyst

Abstract: The activity of a ZrO 2 -supported nickel catalyst promoted by silica (Ni-Si/ZrO 2 ) in CO 2 dry reforming of methane was carried out at 400 and 450 °C. The catalysts were prepared by an impregnation method and characterized by H 2 -TPR, XRD, TEM, TG-MS, Raman, XPS, and in situ XPS and DRIFTS. It was discovered that Ni-Si/ ZrO 2 showed higher initial conversion of CH 4 (0.50 s −1 ) and CO 2 (0.44 s −1 ), and stability for low temperature (400 °C) DRM reaction in comparison to an SiO 2 -supported nickel catalys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
138
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 263 publications
(143 citation statements)
references
References 64 publications
5
138
0
Order By: Relevance
“…Two reduction peaks at about 450 and 650 • C, denominated α and β, respectively, are observed on both catalysts. The first peak (α) corresponds to the reduction of the NiO species of weak and strong interaction with Y and/or Zr [23,27]. This first peak shifts to low temperature on NiO-ZrO m -YO n catalyst, as compared to the NiO-ZrO m catalyst.…”
Section: The Reducibility Of Y-doped and Y-free Nio-zro M Catalystsmentioning
confidence: 98%
“…Two reduction peaks at about 450 and 650 • C, denominated α and β, respectively, are observed on both catalysts. The first peak (α) corresponds to the reduction of the NiO species of weak and strong interaction with Y and/or Zr [23,27]. This first peak shifts to low temperature on NiO-ZrO m -YO n catalyst, as compared to the NiO-ZrO m catalyst.…”
Section: The Reducibility Of Y-doped and Y-free Nio-zro M Catalystsmentioning
confidence: 98%
“…Then, solutions of metal salts (nickel(II) nitrate and/or ruthenium(III) chloride) were added dropwise and the pH was adjusted to 9. The precipitate was separated, washed twice with water, and dried at 80 • C. Obtained powders were calcinated at 400, 500, and 600 • C for Al 2 O 3 , MgAl 2 O 4 , SiO 2 , and ZrO 2 supports [30,41,42], respectively. The metal content used for preparation was 7 wt.% and 1 wt.% for nickel and ruthenium, respectively.…”
Section: Preparation Of Ni and Ni-ru Catalystsmentioning
confidence: 99%
“…Ruthenium nanoparticles were also successfully used for tuning the hydrogen/carbon monoxide molar ratio [16]. The coupling of nickel particles into alloys or spinel structures with other non-noble elements, such as Co [17,18], Cr [18], Mn [18][19][20], Ce [19,21], Fe [22,23], Zr [24], and Al [20,24], and alkali metals, such as Mg [25,26], K [27,28], and Na [29], was also reported as an effective approach to extend catalyst activity and reduce carbon formation [18,30]. Another technique used to preserve the small size of nickel particles is an application of a support that strongly interacts with the active metal.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the metallic Ni nanoparticles can be well-dispersed on the support, which is further conducive to the improvement of the catalytic activity and anti-coke property of the catalyst (Nabgan et al, 2020). Wang Y. et al (2018b) confirmed that the metal-support interaction of the Ni-Si/ZrO 2 catalyst not only facilitated the formation of small metallic Ni active sites with strong electron donor capability but also maintained the state of the Ni particles under CRM reaction conditions.…”
Section: Oxide Supports Single Oxide Supportsmentioning
confidence: 61%
“…Oxide materials, such as CeO 2 (Luisetto et al, 2019), SiO 2 (Zhang L. et al, 2019;de la Cruz-Flores et al, 2020), Al 2 O 3 (Rahbar Shamskar et al, 2017), MgO (Zhou et al, 2018), and ZrO 2 (Wang Y. et al, 2018b), are widely utilized as supports of Nibased catalysts for the CRM process. For example, CeO 2 has been extensively investigated as a support of Ni-based catalysts because of the formation of a strong metal-support interaction, which can contribute to the enhancement of the reactivity by facilitating the CH 4 dissociation over the metallic Ni active site (Yan et al, 2019).…”
Section: Oxide Supports Single Oxide Supportsmentioning
confidence: 99%